Neurosteroid Biosynthesis and Function in the Brain of Domestic Birds - Tsutsui, Kazuyoshi (Frontiers in Endocrinology, 2011)
It is now established that the brain and other nervous systems have the capability of forming steroids de novo, the so-called “neurosteroids”. The pioneering discovery of Baulieu and his colleagues, using rodents, has opened the door to a new research field of "neurosteroids". In contrast to mammalian vertebrates, little has been known regarding de novo neurosteroidogenesis in the brain of birds. We therefore investigated neurosteroid formation and metabolism in the brain of quail, a domestic bird. Our studies over the past two decades demonstrated that the quail brain possesses cytochrome P450 side-chain cleavage enzyme (P450scc), 3beta-hydroxysteroid dehydrogenase/delta5-delta4-isomerase (3beta-HSD), 5beta-reductase, cytochrome P450 17alpha-hydroxylase/c17,20-lyase (P45017alpha,lyase), 17beta-HSD, etc., and produces pregnenolone, progesterone, 5beta-dihydroprogesterone (5beta-DHP), 3beta, 5beta-tetrahydroprogesterone (3beta, 5beta-THP), androstenedione, testosterone, and estradiol from cholesterol. Independently, Schlinger's laboratory demonstrated that the brain of zebra finch, a songbird, also produces various neurosteroids. Thus, the formation and metabolism of neurosteroids from cholesterol is now known to occur in the brain of birds. In addition, we recently found that the quail brain expresses cytochrome P4507alpha and produces 7alpha-and 7beta-hydroxypregnenolone, previously undescribed avian neurosteroids, from pregnenolone. This paper summarizes the advances made in our understanding of neurosteroid formation and metabolism in the brain of domestic birds. This paper also describes what are currently known about physiological changes in neurosteroid formation and biological functions of neurosteroids in the brain of domestic and other birds.